ANALYSIS OF CLONED SEQUENCES AND EXPRESSION OF ASR GENE FAMILY IN MILLET - X.N. Cao; L.H. Shen; J. Song; J.J. Wang; H.G. Wang; 5· L. Chen; Y.X. Pei; S.C. Liu; 5; Z.J. Qiao; 5 . (Journal of Animal and Plant Sciences, 2021)
ABA-stress-ripening (ASR) protein is a hydrophilic plant-specific protein and plays an indispensable role in plant abiotic stress. However, the study of the ASR gene family of millet has not yet been completed. In this study, we identified six members of the ASR family of millet and analyzed their genetic structure, protein alignment and phylogenetic relationships. The PmASR protein was found to contain highly conserved motifs and the millet ASR gene was divided into three groups, namely (1) PmASR1, PmASR2, PmASR5; (2) PmASR3; (3) PmASR4, PmASR6. Three sets of representative ASR gene clones were selected and the transcriptional profiles of PmASR1, 3, 4 genes in various tissues or under different abiotic stresses were quantitatively analyzed by fluorescence. The results showed that the PmASR1 and PmASR3 genes were mainly up-regulated in roots while PmASR4 gene was mainly up-regulated in leaves. And the expression of ASR genes is different under at least one. Therefore, it can be concluded that the ASR gene family in millet was an abiotic stress response gene.
Keywords: Cloning; Millet; ABA-stress-ripening (ASR) protein; Expression patterns